Pension incomes in the European Union: Policy reform strategies in comparative perspective - Daniela Mantovani; Fotis Papadopoulos; Holly Sutherland; Panos O. Tsakloglou (University of Essex, Institute for Social and Economic Research (ISER), 2005)
This paper considers the effects on current pensioner incomes of reforms designed to improve the long-term sustainability of public pension systems in the European Union. We use EUROMOD to simulate a set of common illustrative reforms for four countries selected on the basis of their diverse pension systems and patterns of poverty among the elderly: Denmark, Germany, Italy and the UK. The variations in fiscal and distributive effects on the one hand suggest that different paths for reform are necessary in order to achieve common objectives across countries, and on the other provide indications of the appropriate directions for reform in each case.
Keywords: C81; I30; H55; 330; Pensions; European Union; Microsimulation